Ionic currents and ion channels of lobster olfactory receptor neurons (The Rockefeller University Press, 1989)
The role of the soma of spiny lobster olfactory receptor cells in generating odor-evoked electrical signals was investigated by studying the ion channels and macroscopic currents of the soma. Four ionic currents; a tetrodotoxin-sensitive Na+ current, a Ca++ current, a Ca(++)-activated K+ current, and a delayed rectifier K+ current, were isolated by application of specific blocking agents. The Na+ and Ca++ currents began to activate at -40 to -30 mV, while the K+ currents began to activate at -30 to -20 mV. The size of the Na+ current was related to the presence of a remnant of a neurite, presumably an axon, and not to the size of the soma. No voltage-dependent inward currents were observed at potentials below those activating the Na+ current, suggesting that receptor potentials spread passively through the soma to generate action potentials in the axon of this cell. Steady-state inactivation of the Na+ current was half-maximal at -40 mV. Recovery from inactivation was a single exponential function that was half- maximal at 1.7 ms at room temperature. The K+ currents were much larger than the inward currents and probably underlie the outward rectification observed in this cell. The delayed rectifier K+ current was reduced by GTP-gamma-S and AIF-4, agents which activate GTP-binding proteins. The channels described were a 215-pS Ca(++)-activated K+ channel, a 9.7-pS delayed rectifier K+ channel, and a 35-pS voltage- independent Cl- channel. The Cl- channel provides a constant leak conductance that may be important in stabilizing the membrane potential of the cell.